PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) BOLA CERIA DI TK NEGERI ABDI PRAJA - Hasrianti, Happy Sri; Astrid, Astrid; Nurhayati, Nurhayati; Nabila, Andi Ningsi; Ayustiawati, Ayustiawati; Muna, Siti; Susanti, Siti Misra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The cheerful educational ball game can play an important role in improving the development of fine motor skills in early childhood.. This activity aims to describe the creation and implementation of the Bola Ceria game, where children shake a perforated board so that the ball can enter the hole. The method of the activity applied is qualitative descriptive using observation and documentation techniques. The findings show that this game successfully improves eye-hand coordination, focus, and cooperation among children. This activity was carried out the students of Muhammadiyah University of Buton as part of the community service program (PKM) at TK Negeri Abdi Praja. The children showed great enthusiasm and progress in social and cognitive skills. The play activities also strengthened character values such as cooperation, patience, and sportsmanship. Collaboration between teachers and students supported the formation of a fun learning atmosphere. This game has proven to be a meaningful and efficient active learning tool in education for early childhood